Islamic Psychology and Herbert George Wells (1866-1946) - Hüseyin Çaksen (Penerbit Hellow Pustaka, 2024)
Health has five dimensions, namely physical, social, mental, spiritual, and religious health. “Religious health” is the state of physical, mental, social, and spiritual well-being that occurs by complying with the orders, prohibitions and rules of the true religion that is Islam mentioned by Allah. In conclusion, we would like to emphasize that the most important dimension of health is “religious health” since religion has a substantial role in improving physical, mental, social and spiritual health. Wells summarized Islam 100 years ago as follows: modern religion (Islam) appeals to no revelation, no authoritative teaching, no mystery. The statement it makes is, it declares, a mere statement of what we may all perceive and experience. To this, all true religion, casting aside its hulls of misconception must ultimately come. To it indeed much religion is already coming. Lastly, Islamic psychology is rapidly growing and developing with more academic and clinical training programs around the world; therefore, we strongly believe that Islamic psychology should be integrated with mainstream psychology.